EFFECT OF ADDING DRY YEAST AND FOLIC ACID ON IMPROVING THE PHYSIOLOGICAL AND PRODUCTIVE PERFORMANCE OF QUAIL. - Rasheed, Suha A.; Al Nuaimmi, S. M. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to investigate the different effects of folic acid and/or saccharomyces cerevisiae on different aspects of Japanese quails. Eighty quail chicks were used, divided into four groups (20 chicks each), the first group was the control, treated with normal ration and drinking water. The second group was treated with saccharomyces cerevisiae 2.5% in the ration, the third group was treated with folic acid (5mg/L. in drinking water), whereas the last group was treated with both folic acid and yeast as stated above. All treatments were for seven weeks, then the birds were sacrificed, and blood was collected to undergo the parameters. Results revealed that the treatment with yeast or folic acid significantly (p